Kinetics and mechanism of oxidation of hydroxyurea with hexacyanoferrate(III) ions in aqueous solution - Budimir, Ana, inženjerka kemije (Array, 2009)
Summary: Hydroxyurea (HU) effectively reduces Fe(CN)63− to Fe(CN)6 4− species in neutral and basic aqueous solution via an electron transfer process that includes the formation and subsequent fading out of a free radical, U•(U• ≡ H2N−C(=O)N(H)O•). The EPR spectrum of U• in H2O solutions suggests that the unpaired electron is located predominantly on the hydroxamate hydroxyl-oxygen atom. Visible spectrophotometric data reveal HU as a two-electron donor. Stoichiometry of the studied reaction can be formulated as: 2Fe(CN)63− + NH2CONHOH + ½H2O → 2Fe(CN)64− + CO2 + NH3 + ½N2O + 2H+. Lack of evidence for the formation of NO probably is a consequence of fast dimerization of HNO in comparison with the rate of its oxidation, which is slow due to the low reduction potential of the Fe(CN)63−/ Fe(CN)64− couple. The kinetic of oxidation of HU by Fe(CN)63− was studied using stopped-flow technique, as a function of H+, HU, Fe(CN)63− and Fe(CN)64− concentrations, as well as a function of ionic strength and temperature. The kinetic results reveal that oxidation of HU by Fe(CN)63− proceed via an outer-sphere electron-transfer process. The effect of ionic strength on the reaction rate reveals that NaFe(CN)62− is the reacting species rather than Fe(CN)63− ion. The rate of the redox process was found to be first order with respect to both redox reactants while the H+ concentration dependence make clear that U− is about four orders of magnitude more reactive than HU. The formal reduction potentials for U•/U− and HU•/HU couples were estimated from the kinetic results as +0.47 V and +0.84 V, respectively